Immune-related adverse events in various organs caused by immune checkpoint inhibitors - Naoko Okiyama; Ryota Tanaka (Allergology International, 2022)
Current cancer immunotherapies target immune checkpoint molecules such as the inhibitory receptor programmed cell death-1 (PD-1), one of its ligands, programmed cell death ligand-1 (PD-L1), and cytotoxic T-lymphocyte antigen 4 (CTLA-4), a competitive ligand for CD28 binding to stimulatory receptors CD80 and CD86. Multiple biological drugs use monoclonal antibodies targeting PD-1, PD-L1 and CTLA-4 as cancer immunotherapies. These are termed immune checkpoint inhibitors (ICIs). However, activation of the immune system by ICIs can induce the development of immune-related adverse events (irAEs), which can affect multiple organ systems. The most frequent irAEs are cutaneous and mimic various types of spontaneous skin disorders. Most irAEs are classified as autoimmune conditions mediated by ICI-activated CD8+ cytotoxic T cells, some of which are also related to activated B cells and production of pathogenic antibodies. Interestingly, blockade of CTLA-4 mainly induces activation of T cells and inhibition of Treg cells. On the other hand, the mechanisms underlying anti-PD-1/PD-L1 ICI-induced irAEs are more complicated. PD-1 is a receptor expressed on T and B cells, which binds not only PD-L1, but also PD-L2. The role of PD-L1 is dominant in Th1 and Th17 immunity, while PD-L2 works mainly in Th2 immunity. Better understanding of the mechanisms underlying irAEs will allow for better management of irAEs and improve outcomes and quality of life in cancer patients.